Nasopharyngeal Carcinoma: Clinical Achievements and Considerations Among Treatment Options - Liu, Zheran; Chen, Ye; Su, Yonglin; Hu, Xiaolin; Peng, Xingchen (Frontiers in Oncology, 2021)
Nasopharyngeal carcinoma (NPC) is a severe malignancy arising from the nasopharyngeal epithelium and is southern China's 3rd most common cancer. With the advancement of treatment methods, early-stage NPC patients usually have a better prognosis and more prolonged survival period than those with other malignant tumors. Most treatment failures are due to distant metastasis or a locally advanced stage of NPC in the initial diagnosis. In addition, approximately 10% of patients develop local recurrence, and 10-20% of patients experience distant metastasis after treatment. These patients have a poor prognosis, with a median survival of only approximately 10-15 months. In the rapid development of treatment options, the efficacy and safety of some treatments have been validated and approved for first-line treatment, while those of other treatments remain unclear. The present study aims to provide a comprehensive overview of recent advances in NPC treatment and explain the various therapeutic possibilities in treating locally advanced, recurrent, and metastatic NPC patients.